Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3758/s13421-018-0876-7
|View full text |Cite
|
Sign up to set email alerts
|

Imagery retrieval may explain why recall of negative scenes contains more accurate detail

Abstract: We investigated whether the presence of imagery at retrieval was associated with the finding that negative pictures and scenes are recalled with greater perceptual detail. Participants were presented with 30 scenes taken from the International Affective Picture System that were rated either high or low on valence, but similarly on arousal. Recall was prompted with matched visual or verbal cues. During recall, participants reported any images that came to mind and rated them for vividness, whereas accuracy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Considering the second part of the argument, we see in the results that the negatively valenced stories increase most memory qualities, suggesting that the negative stories are more salient and gripping. This is consistent with earlier memory research: Brewin and Langley (2019) found that negative scenes are remembered more vividly. Altmann et al (2012) note that the negatively valenced stories used in their study were more engaging than positive ones.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the second part of the argument, we see in the results that the negatively valenced stories increase most memory qualities, suggesting that the negative stories are more salient and gripping. This is consistent with earlier memory research: Brewin and Langley (2019) found that negative scenes are remembered more vividly. Altmann et al (2012) note that the negatively valenced stories used in their study were more engaging than positive ones.…”
Section: Discussionsupporting
confidence: 93%
“…The role played by subjective experience is often overlooked, not just in attitude and belief surveys, but in experimental studies. There is growing evidence, for example, that spontaneous visual imagery commonly accompanies many unrelated tasks (Brewin & Soni, 2011;Schlagman & Kvavilashvili, 2008) and is an unacknowledged influence on visual memory task performance (Brewin & Langley, 2018). More generally, it has been noted that there are few if any laws of memory, with performance varying considerably according to the situations, people, and materials involved (Roediger, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The role played by subjective experience is often overlooked, not just in attitude and belief surveys, but in experimental studies. There is growing evidence, for example, that spontaneous visual imagery commonly accompanies many unrelated tasks (Brewin & Soni, 2011; Schlagman & Kvavilashvili, 2008) and is an unacknowledged influence on visual memory task performance (Brewin & Langley, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They attributed this finding to the fact that the films they used were quite short and contained fictitious characters, which might have diminished the films' emotional power. It is also possible that negatively valenced pictures recruit greater attention andas previous research (Brewin & Langley, 2019) has shown-are recalled with greater perceptual detail, which may boost their emotional intensity.…”
Section: Emotion and Modalitymentioning
confidence: 97%